Case report: Treatment of a rare primary cerebellum histiocytic sarcoma with surgery and radiotherapy - Yanchu, Li; Li, Zhang; Qiongwen, Zhang; Jiayu, Duan; Feng, Wang (Frontiers in Oncology, 2024)
BackgroundHistiocytic sarcoma originates in various tissues, including the skin, lymph nodes, gastrointestinal tract, lungs, bone marrow, and central nervous system. Primary central nervous system histiocytic sarcoma (PCNSHS) is exceptionally rare, known for its aggressive behavior and poor prognosis. This report describes a case of PCNSHS in the cerebellum treated with surgery and radiotherapy.Case presentationA 30-year-old woman presented with progressive dizziness and headache. Magnetic resonance imaging scans showed right cerebellar neoplastic lesions approximately 3.6 cm*3.0 cm with cerebral edema and fourth ventricle and brainstem compression. The patient underwent surgical debulking, and the pathological diagnosis was PCNSHS. Two months after the surgery, the patient underwent adjuvant radiotherapy at a dose of 60 Gy. No tumor progression has been observed during the one-year follow-up period.ConclusionsThis case report provides an example of effective central nervous system control using resection and radiation therapy. A review of the literature confirms that surgery alone or combined concurrent or sequential treatment of radiotherapy and chemotherapy is often used; however, the best treatment plan remains unclear. Moreover, the prognosis is poor, with a median survival of six months. Thus, ongoing research aims to better understand the biology of histiocytic sarcomas and find more effective strategies.